MULTI-ORGAN INVOLVED BENIGN METASTASIZING LEIOMYOMA (BML) INVESTIGATED WITH 18F-FDG PET/CT - Tasevski, Slavko; Todorova Stefanovski, Dushica; Ugrinska, Ana (Македонско лекарско друштво = Macedonian medical association, 2023)
Benign metastasizing leiomyoma (BML) is a rare condition characterized by the formation of lesions that may occur in various parts of the body, exhibiting similar pathological characteristics to uterine leiomyoma. Generally, it occurs in the lungs, but it can also affect other organs including the heart, brain, lymph nodes. We present a case of a 74-yearold patient with a history of hysterectomy due to leiomyoma. As a result of a severe abdominal pain, eight years later, she underwent a computed tomography (CT) scan, which showed lesions in the lungs, liver and in the epigastric region. One of the lung lesions was biopsied and the finding was consistent with BML. Consequently, she was referred to our institution for positron emission tomography/computed tomography (PET/CT) using 18-fluoro-2-deoxy-D-glucose (18F-FDG). The findings pointed toward multi-organ lesions with mild 18F-FDG uptake in the thorax and abdomen, one of them infiltrating the ribs. Since there is no standardized treatment for BML, personalized treatment strategy should be involved, based on the hormonal receptor status and the size and location of the tumor. Further investigations are needed to determine the effectiveness of using 18F-FDG PET/CT in the diagnosis and management of BML.
МУЛТИ-ОРГАНСКИ БЕНИГНЕН МЕТАСТАЗИРАЧКИ ЛЕОМИОМ (БМЛ) ИСПИТУВАН СО 18F-FDG ПЕТ/КТ
Keywords: 18F-FDG -PET/CT; leiomyoma; metastasizing; multi-organ